Henry and the chalk dragon - Trafton, Jennifer (Rabbit Room Press, 2017)
Elementary school student Henry draws a chalk dragon that escapes from the chalkboard, and becomes a threat to the entire town of Squashbuckle. It's up to Henry and his friends to save the day.